The Analysis of the Application of Problem Based Learning to Student’s Critical Thinking Skills Material: Data Transmission Error Detection - Mursholihah, Ulfah Awaliah; Hatta, Puspanda; Jumari (Journal of Global Hospitality and Tourism Technology, 2025)
The purpose of Indonesian National Education is to develop the ability and shape the character of the nation based on Pancasila, by implementing an independent curriculum and forming the profile of Pancasila students who believe & fear God Almighty, have global diversity, mutual cooperation, independence, critical and creative reasoning. Indonesian education is presented with various innovative learning models to attract and develop the abilities of 21st century learners. The research conducted aims to analyze the results of the application of the Problem Based Learning learning model on the critical thinking skills of class XI F4 students at SMA N 3 Surakarta as many as 36 students. Based on the results of research conducted using qualitative methods based on questionnaire assessments and student learning outcomes, it was found that the critical thinking skills of students in class XI F4 had a very good category, namely 61% on the results of the questionnaire and 67% on the test of student learning outcomes. Indicators of critical thinking skills of students in class XI F4 get 86% achievement on Advances clarification indicators and inference indicators. Based on the results of the research conducted, it is found that the problem-based learning model is effectively used to build students' critical thinking skills on error detection material in data transmission in class XI F4 SMA N 3 Surakarta.